An evaluation of the agreement between the conservative dual‐criterion method and expert visual analysis. Issue 2 (25th March 2018) - Wolfe, Katie; Seaman, Michael A.; Drasgow, Erik; Sherlock, Phillip
Abstract : The conservative dual‐criterion (CDC) method was developed to standardize the analysis of single‐subject experimental designs data, but to date its accuracy has been evaluated only by comparing results to the statistical parameters of graphs. Our study investigated agreement between expert visual analysts and the CDC method on 66 AB tiers from published multiple baseline graphs. We found strong agreement between the two methods for certain types of graphs and discuss implications of the findings and areas for future research.